Examining students’ satisfaction with an entrepreneurial education application: a case of BMC touch - Abd Hamid, Nur Zainie; Law, Kuan Kheng; Anuar, Azyyati; Isahak Merican, Farah Merican; Abdul Samat, Syafiq (Universiti Teknologi MARA, Kedah, 2025)
With the growing integration of technology in education, Business Model Canvas (BMC) Touch has been introduced to support students in understanding BMC concepts effectively. As a newly developed application, the extent to which BMC Touch contributes to student satisfaction has not been explored. In particular, this study aims to examine the relationship between Perceived Usefulness (PU), Perceived Ease of Use (PEU), application performance, and interface quality with student satisfaction in using the BMC Touch application. The data were collected from a total of 109 undergraduate students enrolled in the Principles of Entrepreneurship (ENT530) course at Universiti Teknologi MARA (UiTM) Kedah Branch who participated in the study. Data were collected through a structured questionnaire measuring the four independent variables and student satisfaction. To analyze the data, correlational analysis was conducted to determine the strength and direction of the relationships among the variables. At the same time, multiple regression analysis was employed to identify the strongest predictor of student satisfaction. Notably, correlational analysis revealed that all four factors, PU, PEU, application performance, and interface quality, had significant positive correlations with student satisfaction. Further multiple regression analysis identified that interface quality and PU as the strongest predictors of student satisfaction. Furthermore, the results directly inform practical improvements to the BMC Touch application by emphasizing the need to enhance both its functionality and design quality to increase student engagement and satisfaction. This study contributes significantly to the field of educational technology, particularly within entrepreneurship education. This is achieved by offering empirical insights into how digital tools like BMC Touch can be optimized to better support entrepreneurial learning experiences and promote more effective technology-driven pedagogy.